Fateful choices ten decisions that changed the world, 1940-1941 - Kershaw, Ian (Penguin Press, 2007)
The newest immensely original undertaking from the historian who gave us the defining two-volume portrait of Hitler, Fateful Choices puts Ian Kershaw?s analytical and storytelling gifts on dazzling display. From May 1940 to December 1941, the leaders of the world?s six major powers made a series of related decisions that determined the final outcome of World War II and shaped the course of human destiny. As the author examines the connected stories of these profound choices, he restores a sense of drama and contingency to this pivotal moment, producing one of the freshest, most important books on World War II in years?one with powerful contemporary relevance.